2018
DOI: 10.1111/jir.12564
|View full text |Cite
|
Sign up to set email alerts
|

Falls resulting in health care among older people with intellectual disability in comparison with the general population

Abstract: Background Falls are common among older people with intellectual disability (ID) and are also a major contributor to injuries in this population. Yet, fall characteristics have only been sparsely studied, and the results are inconsistent. The aim of the present study was to investigate type of falls, places where they occurred and activities that caused them, as well as health outcomes and health utilisation patterns after falls, among older people with ID in comparison with their age peers in the general popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…When a fall resulted in hospitalization, rehabilitation services were provided to enable safe discharge home; however, there was neither multifactorial assessment nor periodic follow‐up as recommended in falls prevention guidelines (Moncada & Mire, ). This is problematic as it has been found that when a fall results in a hospital admission, adults with intellectual disability are more likely to be readmitted within 30 days compared to the general population (Axmon et al, ), making post‐discharge planning and follow‐up management critical in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a fall resulted in hospitalization, rehabilitation services were provided to enable safe discharge home; however, there was neither multifactorial assessment nor periodic follow‐up as recommended in falls prevention guidelines (Moncada & Mire, ). This is problematic as it has been found that when a fall results in a hospital admission, adults with intellectual disability are more likely to be readmitted within 30 days compared to the general population (Axmon et al, ), making post‐discharge planning and follow‐up management critical in this population.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been limited research investigating the best available evidence for reducing falls among people with intellectual disability, evidence suggests that exercise‐based interventions, environmental safety and caregiver education are important to reduce fall‐related injuries (Axmon, Ahlström, & Sandberg, ; Cahill, Stancliffe, Clemson, & Durvasula, ; Van Hanegem, Enkelaar, Smulders, & Weerdesteyn, ). Further large trials are required that evaluate the effects of falls prevention strategies to inform the falls management in people with intellectual disability (Finlayson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Falls occurred twice as often during vital activities among people with intellectual disabilities than in the general population. After a fall, people with intellectual disabilities most often experienced head or leg injuries and were more likely to require specialist care [38]. There is a need to further investigate if osteoporosis is being underdiagnosed, if relevant treatment is provided and if older people with DS are offered resources such as fall prevention similar to those recommended with high priority in national guidelines for the population in general [46].…”
Section: Unplanned Visitspotentially Unmet Health Care Needsmentioning
confidence: 99%
“…People with intellectual disability (ID) experience signs of aging from 35 years old (Connolly 1998) and as such can be considered 'older adults'. A recent study that compared falls rates between people with ID and agematched peers demonstrated that people with ID have almost doubled the rate of falls (Axmon et al 2019). A recent systematic review of falls in people with ID found that the pooled proportion of people with ID who fell was 39% [95% CI (0.35-0.43)] (Ho et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of falls in people with ID found that the pooled proportion of people with ID who fell was 39% [95% CI (0.35-0.43)] (Ho et al 2019). A recent study that compared falls rates between people with ID and agematched peers demonstrated that people with ID have almost doubled the rate of falls (Axmon et al 2019).…”
Section: Introductionmentioning
confidence: 99%